2009
DOI: 10.1002/mabi.200800359
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Human U937 Monocytes to Nitrogen‐Rich Organic Thin Films: Novel Insights into the Mechanism of Cellular Adhesion

Abstract: We present a two-fold study designed to elucidate the adhesion mechanism of human U937 monocytes on novel N-rich thin films deposited by plasma- and VUV photo-polymerisation, so-called "PVP:N" materials. It is shown that there exist sharply-defined ("critical") surface-chemical conditions that are necessary to induce cell adhesion. By comparing the film chemistries at the "critical" conditions, we demonstrate the dominant role of primary amines in the cell adhesion mechanism. Quantitative real-time RT-PCR expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 41 publications
(80 citation statements)
references
References 47 publications
6
74
0
Order By: Relevance
“…[31] Yet, the PPE:N coatings studied here performed quite similarly. Therefore, the choice between PPE:N coatings was made according to their uniformity, their stability and their facility of transfer to real prostheses.…”
Section: Ppe:n Increases Human Umbilical Vein Endothelial Cell (Huvecmentioning
confidence: 77%
“…[31] Yet, the PPE:N coatings studied here performed quite similarly. Therefore, the choice between PPE:N coatings was made according to their uniformity, their stability and their facility of transfer to real prostheses.…”
Section: Ppe:n Increases Human Umbilical Vein Endothelial Cell (Huvecmentioning
confidence: 77%
“…However, in a recent article [8] we have shown that they can be made to adhere to our plasma-or photo-chemically synthesized organic thin ("PE-N") films, provided that the outer surfaces of these coatings contain a minimum ("critical") concentration of 4.2 atomic % of primary amine groups, R-NH2. This is illustrated in Figure 1, where we note that the different surfaces have Now, numerous investigations [10][11][12][13] have been able to unambiguously demonstrate the ability of charged polymer surfaces to bind proteins [12] or living cells [10,11,13] in vitro.…”
Section: Resultsmentioning
confidence: 98%
“…As already mentioned, we selected two well-characterised PVP:N coating-types. Samples were necessarily exposed to ambient air for limited periods of time after deposition; the reader is referred to our earlier reports regarding these materials [24,25,[39][40][41]. The films were chosen for their high amine content and the resulting technological relevance, particularly their good performance in biomedical applications.…”
Section: Resultsmentioning
confidence: 99%